Maladies, preventives, and curatives : debates in public health in India - Bagchi, Amiya Kumar; Soman, Krishna (New Delhi : Tulika Books, 2005)
Contributed seminar articles jointly organized by the Dept. of History, Calcutta University and the Institute of Development Studies, Kolkata on Oct. 2003.
Public health and nutrition : colonial history and current challenges / Amiya Kumar Bagchi and Krishna Soman -- Kala-azar in Assam : British medical intervention and people's response / Achintya Mukar Dutta -- "Cinchona" policy in British India : the critical early years / V.R. Muraleedharan -- Perceptions of public health : a study in British India / Deepak Kumar -- Press and the problem of medical relief in colonial Bengal, 1921-1947 / Kabita Ray -- Continuities and discontinuities in public health : the Indian experience / Imrana Qadeer -- Women's health movement in independent India / C. Sathyamala -- The Indian pharmaceutical industry at the crossroads : implications for india's health care / Amit Ray -- The population questions in West Bengal : in search of a women's perspective / Krishna Soman -- Emerging nutritional trends in India and their implications / R. Radhakrishna and C. Ravi -- Micronutrient malnutrition : some public health concerns / Dilip Mahalanabis.
Includes bibliographical references and index.
Keywords: Public health -- India -- Congresses